Tindak Pidana Kejahatan Penyelundupan Manusia (People Smuggling) di Indonesia: Tanggug Jawab Indonesia dan Australia - Kristin, Debby; Trie Isana Dewi, Chloryne (Padjadjaran Journal of International Law, 2017)
AbstrakPenyelundupan manusia merupakan salah satu kejahatan transnasional terorganisir yang semakin meningkat di Indonesia, khususnya pulau-pulau perbatasan yang letaknya dekat dengan Australia. Lemahnya pengawasan di wilayah perbatasan dan kurangnya pengetahuan masyarakat setempat tentang kejahatan penyelundupan manusia memudahkan pihak-pihak tertentu untuk menyelundupkan para imigran ilegal ke Ashmore Reef (Australia). Sebagai Negara pihak United Nations Convention Against Transnational Organized Crime (UNTOC) dan Palermo Protocol, Indonesia dan Australia mempunyai kewajiban dalam rangka pencegahan dan pemberantasan tindak pidana penyelundupan manusia. Makalah ini adalah untuk menganalisis apakah Indonesia dan Australia telah memenuhi kewajibannya sebagai Negara Peserta UNTOC dan Palermo Protocol, serta memberikan rekomendasi kepada kedua negara dalam melaksanakan kewajibannya terkait kejahatan penyelundupan manusia sebagai bentuk tanggung jawab Negara. Kata kunci: kejahatan transnasional terorganisir, penyelundupan manusia, tanggung jawab negara.AbstractPeople smuggling is one of transnational organized crimes that has been increasing in Indonesia, especially in the outermost Indonesian’s islands which are close to Australia. Lack of surveillance in the border region and lack of knowledge on the local people in regards to the crimes of people smuggling makes it easy to smuggle illegal immigrants to Ashmore Reef (Australia). Hence, it leads to the increasing number of people smuggling in Indonesia. As state parties to the United Nations Convention Against Transnational Organized Crime (UNTOC) as well as its Protocol, Indonesia and Australia bound by the obligation to prevent and combat people smuggling. The purpose of this paper is to analyze whether Indonesia and Australia have fulfil their obligation as State Parties of the UNTOC and the Palermo Protocol, also to propose actions that can be taken by both Governments to fulfill their obligation as state party in regards to the state responsibility. Keywords: people smuggling, state responsibility, transnational organized crime.